Practice and challenges of humanitarian logistics management within the Ethiopian public pharmaceutical supply chain - Biniam Bahiru Tufa; Shiferaw Mitiku Tebeka (BMC Health Services Research)
Abstract Background Humanitarian logistics involves the coordinated movement of relief goods, personnel, information, and funds between beneficiaries, donors, and suppliers, which is crucial for successful emergency response operations. In Ethiopia, logistical challenges often hinder access to healthcare services. This study focuses on humanitarian logistics management (HLM) in Ethiopia, aiming to assess the perceptions of HLM practices, identify key challenges, and provide solutions to improve healthcare access for beneficiaries. Methods An explanatory and descriptive case study design was used to explore the logistical challenges. A mixed-methods approach, combining both quantitative and qualitative data, was employed concurrently. The study surveyed 92 professionals in technical and managerial positions from nine directorates involved in core humanitarian logistics activities, using a census sampling method. Results The study identified 20 key challenges, grouped into five categories. Organizational and economic challenges were the most prominent. The findings revealed notable variations in HLM practices across organizations. Inventory management was the most commonly implemented logistics function, followed by distribution management. In contrast, procurement and transportation management were less effectively practiced. Among the organizations studied, the Ethiopian Public Health Institute demonstrated more effective HLM practices compared to the Ministry of Health and the Ethiopian Pharmaceuticals Supply Service. Conclusions The study highlights significant inefficiencies in the humanitarian logistics system, particularly in procurement and transportation management. These inefficiencies disrupt humanitarian operations, leading to delays in the delivery of pharmaceuticals to beneficiaries. Inadequate logistics can result in loss of life, increased suffering, and unnecessary costs. This research contributes to understanding the gaps in HLM practices in Ethiopia and provides recommendations for improving logistics efficiency in public health emergencies.